CANCER OVARY, PRESENT AND FUTURE OF MANAGEMENT - Pervez, Tariq (Journal of Ayub Medical College Abbottabad, 2003)
Ovarian cancer is very important malignancy of woman as far as its incidence and mortality is concerned. Although majority presents at late stage but still there is a reasonable response to currently available chemotherapy drugs and their use in multimodality setting. Besides good response to chemotherapy drugs, majority have recurrence. So there is a need for new drugs, new trends and their combinations. All these issues will be discussed in this review article